ANALISIS KUALITAS KESADARAN MEREK, ASOSIASI MEREK, DAN LOYALITAS KONSUMEN MI INSTAN - Yohanes Billy Somantri; Leonita Martha Atmadjaja (Universitas Kristen Maranatha, 2019)
In this study the respondents involved are consumers who make a purchase at one of Supermarket in Bandung. The goal of the study was to show brand awareness, quality perceptions, brand associations and brand loyalty that ultimately affect the purchase decision of instant noodles at the supermarket. The results of the study showed that brand awareness, perceived quality, brand association and brand loyalty has affect simultaneously in making the decision of purchasing. The conclusion of the study showed that instant noodles that are not top brand such as sarimi, has brand equity like instant noodle of the top brand. Keywords: Brand Awareness; Brand Equity Brand Loyalty, Perceived Quality; Purchasing Decision